„The End of History” as a Postcolonial Issue: A Polish Perspective - Nakoneczny, Tomasz (Porównania, 2024)
The article provides an outline for a specific thread of the public debate in Poland after 1989. This thread pertains to the use of the civic freedom and state sovereignty regained after the fall of communism, set against the backdrop of center-periphery entanglements, with postcolonial studies serving as the contextual framework adopted in the article. The two poles (centre and periphery) are linked in the interpretative perspective submitted to the reader to two distinctive ideological categories – demoliberalism and identity politics. The universalist dimension of demoliberal ideology and the multifaceted, ethnocentric horizon of identity politics confront each other in the global metadebate (the article cites positions from the Anglo-Saxon world, due to their representativeness and influence), which is also reflected in the Polish debate. The author undertakes to present what he considers to be the most important dividing lines of the debate in question (in the context of its references to the Western centre understood in a postcolonial manner), while refraining from the assumptions about the postcolonial awareness of its participants.